Karakter Keteladanan Profil Pelajar Rahmatan Lil ’Alamin (PPRA) Dalam Program Merdeka Belajar Perspektif Surat Al-Mumtahanah Ayat 4 - Izzan, Ahmad; Iqbal, Muhammad (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
The profile of Rahmatan Lil ‘Alamin students embodies strong national commitment, tolerance towards others, principles rejecting physical and verbal violence, and respect for tradition. PPRA (Preventive Action, Response, and Analysis) emphasizes exemplary values aimed at mitigating the decline in student morals. Surat Al-Mumtahanah verse 4 exemplifies Prophet Ibrahim's commitment to faith despite challenges. This study aims to describe the exemplary character of PPRA in the context of the "merdeka belajar" program from the perspective of Surat Al-Mumtahanah verse 4. This research employs a library research method, examining interpretations of Surat Al-Mumtahanah verse 4 by commentators and written sources on exemplary character by scholars. Using qualitative methods, the study focuses on content analysis of Surat Al-Mumtahanah and textual analysis of relevant literature. The findings highlight that Rahmatan Lil ‘Alamin student profiles reflect universal values and high tolerance. PPRA exemplifies characteristics such as politeness, diligence in learning, heeding advice, and forgiving others' mistakes. In the context of Surat Al-Mumtahanah verse 4, PPRA's exemplary character includes politeness towards others, kindness towards parents, trust in God, earnest prayer, resilience in adversity, receptiveness to advice, restraint from worldly desires, refraining from retaliation, forgiving others, and maintaining positive thoughts about Allah.  Keywords: Exemplary Character, Rahmatan Lil ‘Alamin Student Profile, "Merdeka Belajar" Program.